Straight versus tortuous retinal arteries in relation to blood pressure and genetics. Issue 8 (24th July 2008) - Taarnhøj, N C B B; Munch, I C; Sander, B; Kessel, L; Hougaard, J L; Kyvik, K; Sørensen, T I A; Larsen, M
Abstract : Background/aims: To assess the relative influence of genetic and environmental factors on retinal arterial tortuosity and the association between tortuosity and various health indices in healthy young to middle-aged persons. Methods: This cross-sectional study included 57 monozygotic and 52 dizygotic same-sex healthy twin pairs, aged 20 to 46 years, who were characterised by determination of retinal vessel diameters, arterial blood pressure, blood glucose, body mass index, smoking habits and retinal arterial tortuosity, using a three-level grading scale (straight, wavy, tortuous). Heritability of retinal arterial tortuosity was estimated using structural equation modelling. Results: Of 218 subjects, 79 (36.2%) had straight retinal arteries, 110 (50.5%) had wavy arteries, and 29 (13.3%) had tortuous arteries. Heritability of tortuosity was 82% (CI95 64, 92%), with unshared environmental factors accounting for the remaining 18% (CI95 8, 36%). Increasing values of mean arterial blood pressure and body mass index were both associated with decreasing levels of retinal arterial tortuosity. Conclusion: There was a large variation in tortuosity of retinal arteries in these healthy subjects and the predominant determinant was genetic influence, accounting for 82% of the observed variation in tortuosity.